2017
DOI: 10.7759/cureus.1614
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Fully Synthetic Electrospun Matrix to a Bi-Layered Xenograft in Healing Full Thickness Cutaneous Wounds in a Porcine Model

Abstract: A fully synthetic electrospun matrix was compared to a bi-layered xenograft in the healing of full thickness cutaneous wounds in Yucatan miniature swine. Full thickness wounds were created along the dorsum, to which these matrices were applied. The wound area was measured over the course of healing and wound tissue was scored for evidence of inflammation and healing. Animals were sacrificed at Day 15 and Day 30 and tissue samples from the wound site were harvested for histopathological analysis to evaluate inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Consistent with findings from a previous animal study, the synthetic hybrid-scale fiber matrix resulted in rapid granulation (10). The synthetic matrix is able to support effective granulation due to its architecture, which is engineered to provide a favorable environment for cellular infiltration, neovascularization, and new tissue formation (11).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with findings from a previous animal study, the synthetic hybrid-scale fiber matrix resulted in rapid granulation (10). The synthetic matrix is able to support effective granulation due to its architecture, which is engineered to provide a favorable environment for cellular infiltration, neovascularization, and new tissue formation (11).…”
Section: Discussionsupporting
confidence: 83%
“…As such, a two-stage procedure may be needed for effective wound coverage, with the first step being preparation of the wound bed followed by the second step of application of the STSG. Published studies have reported on the use of various biologic dermal substitutes, including a number of xenografts, prior to application of STSG; however, biologic modalities are associated with risks of disease transmission, marked inflammatory response, and limited availability (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning uses a high voltage (5–30 kV) to produce polymer fibres, with diameters ranging from two nanometres up to several micrometres from a polymer solution or melt [ 22 ]. So far, at least 12 electrospun medical devices are in late stages of regulatory or market approval, with the majority being used as surgical grafts or for tissue regeneration [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. The technique is particularly promising for drug delivery because of its versatility and the high surface area of the resulting nanofibre mesh, which allows an active compound to be incorporated and released at a controlled rate by either diffusion or degradation of the nanofibres [ 3 ].…”
Section: Electrospun Mucoadhesive Materialsmentioning
confidence: 99%
“…3 Pre-clinical evaluation of the hybrid-scale fiber matrix in a porcine model resulted in faster and more complete wound closure with less inflammation and increased neovascularization compared to a commercially-available xenograft control. 4,5 A retrospective clinical study by Regulski et al found that 85% (28 of 34) of DFUs treated with the hybrid-scale fiber matrix achieved complete healing by 12 weeks. 6 Additionally, the retrospective review by Barton et al demonstrated 96% healing rate (22/23) in lower extremity wounds treated with the matrix, with the majority of their patients only requiring a single application.…”
Section: Introductionmentioning
confidence: 99%